Effect of Traditional Chinese Medicine characteristic nursing technology combined with health education on gastrointestinal adverse reactions during chemotherapy in elderly patients with cancer (中医特色护理技术联合健康教育对老年肿瘤患者化疗期间胃肠道反应的影响) - LI Fang (李芳) (Association of Integrative Nursing, 2023)
Objective To investigate the effect of Traditional Chinese Medicine(TCM) nursing technology combined with health education on gastrointestinal adverse reactions during chemotherapy in elderly patients with cancer. Methods Totally84 elderly patients with cancer who received chemotherapy from March 2021 to July 2022 were included and divided into two groups by the random number table method. The control group (n=42) received routine nursing during treatment, while the observation group (n=42) received TCM characteristic nursing technology combined with health education. The gastrointestinal adverse reactions during chemotherapy were observed and analyzed. The psychological state of patients was measured by Self-rating Anxiety Scale (SAS) and Self-rating Depression Scale (SDS). Results The incidences of constipation, loss of appetite, nausea and vomiting in the observation group were lower than those in the control group(P＜0. 05). Scores of SAS and SDS in the observation group were lower than those in the control group after implementation of nursing interventions(P＜0. 01). Conclusion The combination of TCM characteristic nursing techniques and health education has a positive impact on reducing gastrointestinal adverse reactions, and can also alleviate the negative emotions of patients with chemotherapy for cancer. (目的 探讨中医特色护理技术联合健康教育对老年肿瘤患者化疗期间胃肠道反应的影响。方法 选取2021年3月-2022年7月在医院接受化疗的84例老年肿瘤患者为研究对象, 采用随机数字表法分为观察组与对照组。对照组(n=42)接受常规护理干预, 观察组(n=42)开展中医特色护理技术联合健康教育。记录两组患者胃肠道反应发生情况, 采用焦虑自评量表(SAS)和抑郁自评量表(SDS)评估患者心理状态。结果 观察组患者便秘、食欲减退、恶心呕吐等发生率均低于对照组, 差异有统计学意义(P＜0. 05)。护理干预后观察组SAS和SDS量表评分低于对照组, 差异有统计学意义(P＜0. 01)。结论 老年肿瘤患者化疗期间采取中医特色护理技术联合健康教育对减轻胃肠道反应有着积极影响, 且能够缓解患者的负面情绪。)